2013
DOI: 10.1136/bcr-2013-200711
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic kidney disease and chronic renal failure in tuberous sclerosis

Abstract: Tuberous sclerosis is a rare genetic disease which leads to formation of benign tumours in the brain and other organs of the body. It is a multisystem disease with various clinical manifestations. Renal angiomyolipomas are the most common renal manifestations whereas renal cell carcinoma is the least. Renal cysts are found in around 20% of the patients but polycystic kidney disease is present in less than 2% cases and is relatively rare manifestation of the disease. We present a case of tuberous sclerosis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Encroachment into the normal renal tissue, leading to renal failure may occur; but in most patients, as in our case, renal failure was due to PKD or loss of normal renal tissue due to multiple interventions to treat hemorrhage. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Encroachment into the normal renal tissue, leading to renal failure may occur; but in most patients, as in our case, renal failure was due to PKD or loss of normal renal tissue due to multiple interventions to treat hemorrhage. 9 …”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients (more than 80%) with TSC develop some form of kidney disease during their lifetime 10. Angiomyolipoma and cystic kidney diseases are among the common renal manifestations of TSC, with ADPKD occurring only in about 2% of TSC cases 4. The classic ADPKD renal phenotype may occur in the context of TSC disease as a result of large deletions involving the PKD1 and TSC2 genes present on the chromosome 16p13.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal distention and hypertension are common manifestations of ADKPD in these cases 6. Progression to end-stage renal disease (ESRD) has been noted in early ages, even as early as the third decade in some cases, and requires renal replacement therapy 4 11 17 21 22. According to Sampson et al , most patients with non-mosaic deletions in TSC1/PKD2 gene were found to have enlarged cystic kidneys during infancy or childhood with features of advanced ADPKD at the time of diagnosis, but other patients had variable degrees of renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…ADPKD accounts for fewer than 2% of TSC cases ( 33 , 34 ). The phenotypic intersection between TSC and ADPKD cases indicate the existence of a functional relationship between the respective genes that have been recently identified as the mTOR signal pathway ( 35 ).…”
Section: Pathophysiologymentioning
confidence: 99%